The Impact of Presupposition in Diplomatic Language: Kurdistan Region as a case study - Ahmed, Trife Omer; Salih Berznji, Dana Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Generally, researching the link between language and other topics can be classified under applied linguistics. Few academic articles have studied the connection of language with politics and diplomacy, yet even fewer in Kurdish language. Within this discipline, the diplomatic language, considered as the meeting point of language and diplomacy, is a purely practical subject. It is used by diplomats and politicians for rapprochement and solving problems of misunderstanding and to reach agreement and other purposes. Based on the perceived importance of this subject, this research studies diplomatic language presupposition effects and how it is used in the Kurdistan Region. Thus, this research represents an academic effort at learning how to master diplomatic language according to the bases of presupposition as a subject in the semantic and pragmatic sciences. This research attempted to verify the validity of a binary hypothesis and prove its validity, i.e. the effect of the presupposition generally depends on the formulation of prior information. The more it is formulated towards achieving the objectives of the diplomat, the more its effect will be positive, and vice versa. In relation to the diplomatic language used by decision-makers in the Kurdistan Region, it is not deduced from the presupposition techniques which is a solid basis for establishing relations, but rather a negative language that enjoys the minimum rules of presupposition in directing its messages, as it is a declarative or a narrative language in the form of regularity and the provision and repetition of information. Therefore, the weakness of the diplomatic language was a reason behind the weakness in diplomatic relations related to the demands of the Kurdistan Region. This research utilizes the descriptive - analytical approach and takes the Kurdistan Region as a case study and it consists of an introduction and two sections. The theoretical aspect of the presupposition and the diplomatic language is researched in the first section, and the second is devoted to addressing the Kurdistan Region’s position in the diplomatic field and analyzing the presupposition used in a sample of the diplomatic language for official decision-makers. Then, the results are presented according to an analysis of the data that shows the weakness of presupposition. The main result is that the weakness of the diplomatic language of the Kurdistan Region officials was one of the reasons for the weakness of diplomatic relations which in turn was caused by the ineffective use of presupposition.